2020
DOI: 10.1063/1.5143450
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure behavior of a linear chain alkane, tricosane

Abstract: Exploring the behavior of hydrocarbon under pressure is important for understanding its role in planetary sciences and also for exploring novel organic chemistry. In this study, we explored the high-pressure behavior of a linear-chain hydrocarbon, tricosane (C23H48), using Raman spectroscopy. We compressed tricosane up to 23 GPa and did not find any evidence for pressure-induced amorphization within the conditions explored in this study. Upon compression, we observe new modes in the low energy region 100–300 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 47 publications
4
36
0
Order By: Relevance
“…At high pressures, although, a transition to a hairpin/folded state appears unlikely based on a comparison between the observed and calculated spectra (Figure ). Our results on octadecane are similar to a recent study on tricosane (C 23 H 48 ), which also reveal pressure-induced new low wavenumber modes, albeit at a lower pressure of 0.3 GPa . The appearance of the new modes was attributed to bent-chain configurations .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…At high pressures, although, a transition to a hairpin/folded state appears unlikely based on a comparison between the observed and calculated spectra (Figure ). Our results on octadecane are similar to a recent study on tricosane (C 23 H 48 ), which also reveal pressure-induced new low wavenumber modes, albeit at a lower pressure of 0.3 GPa . The appearance of the new modes was attributed to bent-chain configurations .…”
Section: Discussionsupporting
confidence: 90%
“…Aside from the appearance of the low wavenumber modes around 4–5 GPa, no other distinct changes in the spectral pattern were observed that would be indicative of a transformation/dissociation to a different compound. Similar phase stability as a function of pressure was observed for tricosane to 23 GPa . The phase stability of C 18 and C 23 over a large range of pressure indicates that the aliphatic hydrocarbons, likely, would have survived the impact experienced by the interplanetary dust particles or microsized meteorites during the exogenous delivery of organic matter in the late heavy bombardment period (4.5–3.8 Ga).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations